Determinan Potensi Fraud Dalam Pengelolaan Dana Desa Akibat Pandemi Covid-19 Pada Desa - Novita Sari; Ratna Sari Dewi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect of village apparatus competence, internal control, and organizational commitment to the potential for fraud in the management of village funds in Serdang Bedagai Regency. This type of data in this study is quantitative data using a questionnaire as a means of obtaining data. This research was conducted in the village of Perbaungan sub-district Serdang Bedagai Regency as many as 24 villages. The population and sample in this study were 120 people, 5 people each in each village. The data analysis method used in this study is the method of multiple linear regression analysis carried out with the help of SPSS software. The results of this study found that apparatus competence have a significant influence on the potential for fraud in the management of village funds in Serdang Bedagai Regency. While internal control and organizational commitment have no effect on the potential for fraud in the management of village funds in Serdang Bedagai Regency. On other results, it can be seen that simultaneously all independent variables have a significant influence on the potential for fraud in the management of village funds in Serdang Bedagai Regency.